Drawing up a Health Services Waste Management Plan: Strategies and Impacts - Gomes, Fabiana Silva; Silva, Élida Maria da; Sá , Stone de; Mello, Dirceu Raposo de; Martins, José Luis Rodrigues (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
The management of Health Services Waste (HSW) is fundamental for the protection of public health and the environment. The objective of this study was to prepare a Health Services Waste Management Plan (HCWMP) for the Evangelical University of Goiás, Ceres Campus, located in the city of Ceres, Goiás, focusing on waste management strategies and reduction of environmental impact. The methodology adopted was exploratory, using the Web of Science database, which included articles from 2020 to 2024, and descriptive, analysing the waste generated at the university between August and November 2024. The results showed significant improvements after the implementation of the HCWMP, namely the creation of an exclusive room for the storage of waste, the reduction of contamination risks and compliance with legal regulations, such as CONAMA Resolution 358/05, as well as a reduction in the amount of waste distributed of up to 52% for Group A (infectious waste), 39% for Group B (chemical waste) and 9% for Group E (sharps materials). These data underline the importance of implementing the HCWMP for more efficient waste management, reducing the total volume collected and improving the separation of different types of materials. We conclude that the implementation of the HCWMP represents a significant milestone in optimising laboratory waste management, with benefits for public health and environmental protection. In this way, the HCWMP implemented at the Ceres campus has established itself as an effective model for sustainable waste management in the healthcare sector, providing an example that can be replicated in other institutions and reinforcing the importance of environmental education and training to ensure that its benefits are sustainable in the long term.